„Az igaz ember hitből él” (Róma 1,17) – a hit, mint a református önértelmezés fő alkotóeleme - Sarolta PÜSÖK (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The Just Shall Live by Faith. (Romans 1,17) – Faith, as the Main Factor of the Reformed Identity.